3-D printed sets and props: How designers integrate digital technologies - Bevan, Alexandra (Convergence (London, England), 2018)
The article addresses how production designers and artists experience the shift to digital fabrication tools, relying on two industry interviews and trade publications. My intervention highlights the importance of the designer’s experience of the digital transition, which has been neglected by scholarship to date on digital technologies in the media industries.